Socio-Cultural Activity Planning of Culture and Arts Manager Characteristics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article describes the culture and art manager's work, the requirements for him, his role in the development of the organization today, the procedure for planning his activities, and the goals and tasks of the work processes.